PENGARUH MODEL PEMBELAJARAN GUIDED DISCOVERY LEARNING TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA - Hadini, Lia; Trio Pangestu , Widya (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the significant effect of the guided discovery learning model on students' critical thinking skills. This study used a quantitative method with a quasi-experimental design of the nonequivalent control group type. This study was conducted at the UPTD of Burneh 1 Public Elementary School, using a population of fourth-grade students from the 2025/2026 academic year using a purposive sampling technique. Data collection techniques included interviews, observation, documentation, and a critical thinking ability test. Data analysis used an independent sample t-test. The results showed that a comparison of two independent samples obtained an average critical thinking ability (posttest) score of 74 students in the experimental class using the guided discovery learning model and an average critical thinking ability (posttest) score of 63 students in the control class not using the guided discovery learning model. The calculation results of the independent sample t-test obtained a significance value of 0,001. Based on the testing criteria, if the significance value is less than 0,05, H0 is rejected and Ha is accepted. Therefore, it can be concluded that the guided discovery learning model has an effect on students' critical thinking skills.